LED based lighting and communications: An emerging technology for a greener more sustainable future - Burton, A.; Minh, H. Le; Aslam, N.; Le, L.; Nguyen, T. D. (EAI Endorsed Transactions on Energy Web, 2017)
The paper discusses on the effect that the growth in our energy consumption as a species is having upon the planet, and how the global lighting and telecommunications industries are major contributors. We demonstrate that through the adoption of LED based lighting combined with visible light communications, substantial economical and power savings by orders of magnitude can be made over existing technologies, contributing towards a greener more sustainable future. The future of LED technology is also discussed with a focus on organic technology, promising increased savings.
Keywords: LED; OLED; VLC; green technology